2006
DOI: 10.1007/s00421-006-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related fatigability of the ankle dorsiflexor muscles during concentric and eccentric contractions

Abstract: This study compares the fatigability of the ankle dorsiflexors during five sets of 30 maximal concentric and eccentric contractions in young and elderly adults. The torque produced by the ankle dorsiflexors and the average surface electromyogram (aEMG) of the tibialis anterior were continuously recorded. The contribution of central and peripheral mechanisms to muscle fatigue was tested before, after each set of contractions, and during a 30 min recovery period by the superimposed electrical stimulation method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
115
4
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 46 publications
12
115
4
3
Order By: Relevance
“…To avoid these confounding factors when comparing muscle activation during the two anisometric contractions, many studies have used isokinetic dynamometers to control the force and joint angular velocity (Aagaard et al, 2000;Amiridis et al, 1996;Babault et al, 2001;Baudry et al, 2007;Beltman et al, 2004;Duclay and Martin, 2005;Duclay et al, 2011;Grabiner and Owings, 2002;Pasquet et al, 2006;Pinniger et al, 2003;Westing et al, 1990). Nonetheless, the strategy employed by the central nervous system (CNS) when resisting the force imposed by a torque motor can differ slightly from that used when lowering an inertial load to match an imposed trajectory (Duchateau and Enoka, 2008).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…To avoid these confounding factors when comparing muscle activation during the two anisometric contractions, many studies have used isokinetic dynamometers to control the force and joint angular velocity (Aagaard et al, 2000;Amiridis et al, 1996;Babault et al, 2001;Baudry et al, 2007;Beltman et al, 2004;Duclay and Martin, 2005;Duclay et al, 2011;Grabiner and Owings, 2002;Pasquet et al, 2006;Pinniger et al, 2003;Westing et al, 1990). Nonetheless, the strategy employed by the central nervous system (CNS) when resisting the force imposed by a torque motor can differ slightly from that used when lowering an inertial load to match an imposed trajectory (Duchateau and Enoka, 2008).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…However, there are far fewer studies focusing on age-related fatigability for dynamic as compared with isometric contractions. During moderate to fast isotonic concentric tasks, older adults are more fatigable than young (Christie et al 2011;Power et al 2013), but results are variable when reported for isokinetic tasks (Baudry et al 2007;Rawson 2010;Callahan and KentBraun 2011;Dalton et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that used constrained velocity (i.e., isokinetic) tasks and thus defined fatigue as a loss of torque have reported the same (Laforest et al 1990;Callahan et al 2009;Dalton et al 2012), less (Lanza et al 2004;Rawson 2010), or more (Baudry et al 2007;Callahan and Kent-Braun 2011) fatigue in older adults compared with young. Explaining the variability among these studies that used isokinetic tasks, and in comparison with those that have used isotonic tasks, is challenging due to the range of angular velocities tested.…”
Section: Introductionmentioning
confidence: 99%
“…28 For healthy old adults who show initial decrements in voluntary activation, practicing maximal contractions may increase voluntary activation to levels similar to those of young adults. 4,22,25 Exercise-induced impairment of voluntary activation, or central fatigue, 13 contributes significantly to impairment of force during and after long-duration, low-force contractions in young adults and varies with contraction intensity. 44,49 It is not clear, however, whether old adults have greater exercise-induced impairment of voluntary activation than Abbreviations: ANOVA, analysis of variance; CV, coefficient of variation; EMG, electromyography; MVC, maximal voluntary contraction; RPE, rating of perceived exertion; RMS, root mean squared…”
mentioning
confidence: 99%
“…Dorsiflexor muscles and a submaximal intermittent protocol with the elbow flexor muscles showed no age differences in central fatigue. 2,4,34 Several muscle groups, however, exhibit age-related central fatigue including the knee extensor muscles and sustained contractions with the elbow flexor muscles. 5,6,22,46 The magnitude of age-related central fatigue appears to be influenced by the type of contraction during which voluntary activation is assessed.…”
mentioning
confidence: 99%